The Cytoprotective Effects of Human Endothelial Progenitor Cell-Conditioned Medium against an Ischemic Insult Are Not Dependent on VEGF and IL-8. Issue 4 (April 2016) - Di Santo, Stefano; Fuchs, Anna-Lena; Periasamy, Ramesh; Seiler, Stefanie; Widmer, Hans Rudolf
Endothelial progenitor cells (EPCs) promote revascularization and tissue repair mainly by paracrine actions. In the present study, we investigated whether EPC-secreted factors in the form of conditioned medium (EPC-CM) can protect cultured brain microvascular endothelial cells against an ischemic insult. Furthermore, we addressed the type of factors that are involved in the EPC-CM-mediated functions. For that purpose, rat brain-derived endothelial cells (rBCEC4 cell line) were exposed to EPC-CM pretreated with proteolytic digestion, heat inactivation, and lipid extraction. Moreover, the involvement of VEGF and IL-8, as canonical angiogenic factors, was investigated by means of neutralizing antibodies. We demonstrated that EPC-CM significantly protected the rBCEC4 cells against an ischemic insult mimicked by induced oxygen–glucose deprivation followed by reoxygenation. The cytoprotective effect was displayed by higher viable cell numbers and reduced caspase 3/7 activity. Heat inactivation, proteolytic digestion, and lipid extraction resulted in a significantly reduced EPC-CM-dependent increase in rBCEC4 viability, tube formation, and survival following the ischemic challenge. Notably, VEGF and IL-8 neutralization did not affect the actions of EPC-CM on rBCEC4 under both standard and ischemic conditions. In summary, our findings show that paracrine factors released by EPCs activate an angiogenic and cytoprotective response on brain microvascular cells and that the activity of EPC-CM relies on the concerted action of nonproteinaceous and proteinaceous factors but do not directly involve VEGF and IL-8.